A serial mediation model for investigating the intention to use algorithmic trading platforms among retail investors in India - Bhumika Bunkar; Kasilingam Ramaiah (Vilakshan (XIMB Journal of Management))
Purpose – In developing nations, the utility and intention to use algorithmic trading (AT) platforms and financial services are predominantly reliant on investors’ technological knowledge. This study aims to investigate the effect of investor awareness of AT (AAT), trust in AT (TAT), and acceptance of innovativeness (AOI) on intention to use the AT (IUAT) platforms among Indian investors. Design/methodology/approach – The authors used a structured questionnaire with a five-point Likert scale to collect the data from 392 Indian retail investors through a purposeful sampling approach. And, the authors carried out structural equation modeling to analyze the serial mediation among the latent (independent) and observed (dependent) variables. Findings – The findings suggest that investor awareness exerts a statistically significant and positive effect on the IUAT platforms. Additionally, TAT platforms and innovation acceptance, independently as well as mediator, significantly influences the usage decision of AT platforms among Indian investors. Research limitations/implications – The findings on determinants of AT platform usage can guide investment regulators to promote technological awareness, build trust, and provide a safe algorithmic trading environment for retail investors in India. The suggestions may take the edge off a few behavioural impediments among the investors w.r.t. AT platform usage. Originality/value – Off the back of extensive literary exploration our field research is among the first that probes an intellectual discourse and documents the empirical evidence on linkages between investor AAT, TAT, AOI and the IUAT platforms in the Indian stock market.